EEG Assessment in Patients With Disorders of Consciousness: Aims, Advantages, Limits, and Pitfalls - Rossi Sebastiano, Davide; Varotto, Giulia; Sattin, Davide; Franceschetti, Silvana (Frontiers in Neurology, 2021)
This study presents a brief review of literature exploring simple EEG-polygraphic examinations and procedures that can be carried out at a patient's bedside. These include EEG with a common electrode array and sleep evaluation. The review briefly discusses more complex analytical techniques, such as the application of advanced EEG signal processing methods developed by our research group, to define what type of consistent markers are suitable for clinical use or to better understand complex patient conditions. These advanced analytical techniques aim to detect relevant EEG-based markers that could be useful in evaluating patients and predicting outcomes. These data could contribute to future developments in research.